RANCANG BANGUN OTOMASI GENSET 1PHASA 2200VA MENGGUNAKAN AUTOMATIC TRANSFER SWITCH BERBASIS MIKROKONTROLER: Proses perubahan catu daya dari PLN ke genset ataupun dari genset ke PLN secara otomatis merupakan sebuah proses yang disebut dengan Automatic Transfer Switch. Pengontrolan alat tersebut supaya bisa secara otomatis bisa digunakan dengan mikrokontroler yaitu Arduino Mega 2560.Adapun tujuan dari pembuatan otomasi genset 1 phasa dengan Automatic Transfer Switch berbasis mikrokontroler adalah m - Mhd.Abdurrazzaq; Syahrizal (ABEC Indonesia, 2021)
The process of changing the power supply from PLN to generator or from generator to PLN automatically is a process called Automatic Transfer Switch. Controlling the device so that it can automatically be used with a microcontroller, namely Arduino Mega 2560. Arduino will drive control components such as relay modules, ZMPT101B, RTC DS3231 which become digital inputs and analog inputs. The purpose of making an Arduino-based Automatic Transfer Switch is to make a generator ignition system and control the transfer of the power supply automatically using a microcontroller. The purpose of making an automatic generator ignition system is so that users do not need to turn on and off the generator manually, in an automatic way that is controlled via Arduino. The purpose of making 1-phase generator automation with an Automatic Transfer Switch based on a microcontroller is to make it easier for users to turn on and turn off generators automatically and make it easier to transfer power supplies from PLN to generators or from generators to PLN. The generator heating process can also be done automatically which aims to extend the life of the generator. Keywords: ATS, PLN, Genset, UPS, Mikrokontroler